A PENGUATAN PERAN KEWIRAUSAHAAN PERUSAHAAN MENINGKATKAN KINERJA OPERASI LPD MELALUI BUDAYA ORGANISASI BERBASIS TRI HITA KARANA - Riana Dewi Kartika; Ni Made Wulan Sari Sanjaya (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The LPD Supervisory Agency report stated that LPD profits in Buleleng Regency in 2021 decreased by 2 billion rupiah compared to 2020. The decline in profits was the result of the inability of the community to pay credit based on loans at the LPD. Many people have lost their jobs, especially in the tourism sector, which is the cause of the Covid 19 pandemic, which certainly affects the performance of the LPD in Buleleng Regency. This study examines the role of entrepreneurship, hita karana-based organizational culture, and competitive advantage to improve LPD operating performance in Buleleng district. The subject of this research is village credit institution (LPD) in Buleleng district, Bali Province. The data analysis technique uses the GSC-based sem method. The results showed that the first hypothesis was accepted, namely the positive and significant influence of corporate entrepreneurship on the competitive advantage of LPDs in Buleleng Regency. The second hypothesis is rejected, which states that entrepreneurship has an effect on LPD operating performance in Buleleng Regency. The research findings also show that competitive advantage has a significant effect on the operational performance of the LPD in Buleleng Regency. The results of the study show that organizational culture based on tri hita karana has a significant effect on the operational performance of LPD in Buleleng Regency. The results of the analysis also show that the tri hita karana-based organizational culture strengthens the relationship between the company's entrepreneurship and operating performance.